1917
DOI: 10.1021/ja02248a003
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Surfaces of Liquids, and Solubility as Related to the Work Done by the Attraction of Two Liquid Surfaces as They Approach Each Other. [Surface Tension. V.]

Abstract: The experimental work of this paper was begun by E. C. Humphery in 19x2, and was continued in 1913 by F. E. Brown. The delay in its publication has been caused by the fact that until recently WE had not determined accurately the corrections in-'H20 = 72.05, 'CsHs = 28.17, 'HzO.CsHs = 34.68,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

1933
1933
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(29 citation statements)
references
References 0 publications
2
25
0
2
Order By: Relevance
“…The extent of water self association due to LW interactions can be estimated from interfacial-tension-component theory and measurement of interfacial tensions between water (phase 1) and saturated hydrocarbons (phase 2) for which no AB interaction across the interface between phase 1 and 2 (12) is possible. Choosing hexane as an example, it is found experimentally that γ2ν=γ2νitalicLW=18.4mJnormalm2 and γ12italicLW=51.1mJnormalm2 [171, 172]. Using 72.8mJnormalm2=γnormal1νLW+γnormal1νAB for water at 20 °C in the traditional geometric-mean equation (γ12=γ1ν+γ2ν2γ1νitalicLWγ2νitalicLW) [171, 173, 174] calculates that γ1νitalicLW=21.8mJnormalm2, or about 29% of the total interfacial tension of water.…”
Section: 0 Technical Backgroundmentioning
confidence: 99%
“…The extent of water self association due to LW interactions can be estimated from interfacial-tension-component theory and measurement of interfacial tensions between water (phase 1) and saturated hydrocarbons (phase 2) for which no AB interaction across the interface between phase 1 and 2 (12) is possible. Choosing hexane as an example, it is found experimentally that γ2ν=γ2νitalicLW=18.4mJnormalm2 and γ12italicLW=51.1mJnormalm2 [171, 172]. Using 72.8mJnormalm2=γnormal1νLW+γnormal1νAB for water at 20 °C in the traditional geometric-mean equation (γ12=γ1ν+γ2ν2γ1νitalicLWγ2νitalicLW) [171, 173, 174] calculates that γ1νitalicLW=21.8mJnormalm2, or about 29% of the total interfacial tension of water.…”
Section: 0 Technical Backgroundmentioning
confidence: 99%
“…Langmuir (49) in 1917 (cf. Harkins [50][51]) showed that some lipid molecules were amphiphilic (52), in having a polar head and a nonpolar carbon chain. When spread at an air-water interface, they formed a monolayer on the surface and affected the surface tension .…”
Section: Historical Background Before the Electron Microscope E A R Lmentioning
confidence: 99%
“…CC BY 4.0 License. (Richards and Coombs, 1915) Ethyl Acetate 23.246 0.069 23.95 (Mumford and Phillips, 1950) Acetonitrile 27.888 0.064 29.04 (Harkins et al, 1917) Glycerol 63.686 0.057 64.800 (Vargo et al, 1991) Pure Water 70.335 0.089 72.703 (Vargaftik et al, 1983) Salt Water 71.478 0.092 74.876 (Nayar et al, 2014) https://doi.org/10.5194/os-2019-87 Preprint. Discussion started: 1 August 2019 c Author(s) 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Surface tension was measured using Du Noüy Ring tensiometry (Harkins et al, 1917;Noüy, 1925) performed using an Attension Sigma 70 instrument with thermocouple (density resolution: 1 x 10 -4 g cm -3 , force resolution: 0.1 μN) which was calibrated daily. The short-term precision of the instrument, as measured from ~100 repeat measurements, was typically 0.05-0.1 mN m -1 .…”
Section: Surface Tension Measurementsmentioning
confidence: 99%